2013
DOI: 10.1021/ml400144e
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cage-Shaped Structure of Physalins to Their Mode of Action in Inhibition of NF-κB Activation

Abstract: A library of oxygenated natural steroids, including physalins, withanolides, and perulactones, coupled with the synthetic cage-shaped right-side structure of type B physalins, was constructed. SAR studies for inhibition of NF-κB activation showed the importance of both the B-ring and the oxygenated right-side partial structure. The 5β,6β-epoxy derivatives of both physalins and withanolides showed similar profiles of inhibition of NF-κB activation and appeared to act on NF-κB signaling via inhibition of phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…An error bar indicates standard deviation. The authentic compounds used in this analysis were chemically synthesized as described in our previous paper (Ozawa et al, 2013). The limit of detection of each sample was 0.011923 ( P. alkekengi , d15_Young), 0.010910 ( P. alkekengi , d20_Mature), 0.013556 ( P. alkekengi , d22_Mid), 0.010820 ( P. alkekengi , d27_Mature), 0.010884 ( P. alkekengi , d30_Mid), 0.012211 ( P. peruviana , d15_Mature), 0.012456 ( P. peruviana , d22_Mature), 0.012366 ( P. peruviana , d29_Mature), 0.014794 ( P. peruviana , d65_Young), and 0.013141 ( P. peruviana , d65_Mature).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An error bar indicates standard deviation. The authentic compounds used in this analysis were chemically synthesized as described in our previous paper (Ozawa et al, 2013). The limit of detection of each sample was 0.011923 ( P. alkekengi , d15_Young), 0.010910 ( P. alkekengi , d20_Mature), 0.013556 ( P. alkekengi , d22_Mid), 0.010820 ( P. alkekengi , d27_Mature), 0.010884 ( P. alkekengi , d30_Mid), 0.012211 ( P. peruviana , d15_Mature), 0.012456 ( P. peruviana , d22_Mature), 0.012366 ( P. peruviana , d29_Mature), 0.014794 ( P. peruviana , d65_Young), and 0.013141 ( P. peruviana , d65_Mature).…”
Section: Resultsmentioning
confidence: 99%
“…The authentic samples of withanolides were isolated from plants as described in our previous paper (Ozawa et al, 2013). The leaves of P. alkekengi and P. peruviana were collected at five different developmental stages of the growing season before bearing fruit, because our pilot study showed to detect withanolides of P. alkekengi and P. peruviana at these stages (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already succeeded in synthesizing the cage‐shaped molecule 3 (Scheme ),, and we confirmed that the right‐side structure of physalins indeed contributes to NF‐κB‐inhibitory activity . The synthesis of 3 featured precise construction of tricyclic key intermediate 8 through a Diels−Alder reaction and the installation of two C1 units, and its “domino ring transformation”, leading to DEFGH‐ring compound 3 .…”
Section: Introductionmentioning
confidence: 53%
“…Thus, the benzyl group was employed as a protective group for the secondary alcohol at C13 and could be removed by hydrogenolysis to give 42 . Moreover, by utilizing the instability of the H ring, the benzyl‐protected right‐side partial structure of type A physalins (PAright‐1, 62 ) was also synthesized [35]…”
Section: Extracting the Latent Functions: Right‐side Partial Structurmentioning
confidence: 99%